2012
DOI: 10.1136/injuryprev-2012-040580d.21
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Child Maltreatment: Is There a Need for a European Policy?

Abstract: Background The United Nations Secretary-General's report on violence against children has heightened awareness in countries of the victimisation of children worldwide. The response has been greater emphasis on child protection rather than primary prevention. Purpose To raise the level of debate about the need for European wide policy on the primary prevention of child maltreatment. Methods Policy analysis based on documents, survey of health ministry focal persons and age standardised mortality rates. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
115
3
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(146 citation statements)
references
References 0 publications
7
115
3
21
Order By: Relevance
“…Similarly, Gálová (2007) listed some decorative and poisonous houseplants among risk factors for poisoning. Sethi et al (2008) pointed to the fact that children are at a higher risk for poisoning if hazardous substances are inadequately stored and in the reach of children. We found that most parents keep hazardous substances in a high place, out of the reach of children.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Gálová (2007) listed some decorative and poisonous houseplants among risk factors for poisoning. Sethi et al (2008) pointed to the fact that children are at a higher risk for poisoning if hazardous substances are inadequately stored and in the reach of children. We found that most parents keep hazardous substances in a high place, out of the reach of children.…”
Section: Discussionmentioning
confidence: 99%
“…The ecological framework offers a valuable theoretical structure for understanding the abovementioned risk factors of elder abuse because it delineates the different levels (individual/micro/exo/macro) at which abuse 6 occurs (Sethi et al, 2011). Originally, it was developed by Bronfenbrenner (1979) for research on human development, but it has since been widely adopted in other disciplines to understand and describe the context in which a phenomenon occurs or as a framework for data analysis: e.g.…”
Section: The Ecological Framework: Risk Factorsmentioning
confidence: 99%
“…in child abuse (e.g. Belsky, 1980), intimate partner violence (Akhter & Wilson, 2015;Weeks & Leblanc, 2011), violence against women (Heise, 1998) as well as in research on elder abuse (Schiamberg & Gans, 2000;Sethi et al, 2011;Von Heydrich, Schiamberg & Chee, 2012;WHO, 2010). The ecological framework employs a multi-dimensional and multi-faceted view of interpersonal violence.…”
Section: The Ecological Framework: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations